Knowledge Cities: ICT and Urban Components - Cueva Ortíz, Sonia (2021)
Based on a shift in the production matrix from goods and services to knowledge and innovation, countries on at least three continents have invested in the construction of knowledge cities. However, to what extent are knowledge cities (KCs) linked to the information and communications technology (ICT) on which they are based? Are KCs a technological consequence, or a political ideology oriented towards the reinforcement of an economic system? To answer these questions, three global examples and the 22@Barcelona case study were examined using qualitative methods. The findings revealed how political agreements and the modification of urban plans impacted the cities. We observed existing relationships among ICT, KCs, and the business structure that was implemented, although the latter was not part of the KCs. This study presents a theoretical input for KCs and highlights the need for new urban and architectural spaces that respond to the innovative milieu of nascent societies.